Saudi Women Activism through Media - Priyanka Mittal (5115869) (2023)
The article argues that despite the conservative nature of Saudi society, women in Saudi Arabia have been able to use media platforms for their rights-based activism. Women in these restricted and limited spaces have been articulating their self-expression within the limits and confines of the state. This article traces the changing position of women in Saudi society after the 9/11 attacks and Arab uprising. Further, it critically analyzes how Vision 2030 contributes to women’s relaxing laws and position inside the country. The chapter cites various instances to support the argument that Saudi women use media platforms to promote activism for rights, greater social freedom, and more inclusion. Other Information Published in: Social Change and Transformation in the Gulf Region License: https://creativecommons.org/licenses/by/4.0 See chapter on publisher's website: https://dx.doi.org/10.1007/978-981-19-7796-1_37